Ghana - Rajasthan's Bird Sanctuary - Singh, Kailash (Indian Forester, 1958)
Rajasthart's 1!ird Sanctliaty, Keola Ghana situated at Bharatpur is famous for the opportunity it offers for the scientific study of the biology of water-birds. It is a shallow inland lake' where thousads of local water-birds flock during the monsoon foo breedillg and a large number of migratry duckS and other water-birds arrive from far distant places for the winter. The: nesting habits of the birds are most interesting to observe. A forest rest-house accommodates tourists and provides all facilities for stay and excursions.